PERAN FAKTOR INTERNAL DAN EKSTERNAL TERHADAP AUDIT DELAY - SUGIARTO, ROBBY (: 2303-1719)
The accuracy of financial statements is influenced by internal and external factors. Internal factors consist of profitability, solvency, and the size of the company, while external factors consist of size public accounting firm, the auditor's opinion and the existence of the audit committee. Profitability announcement contains good news that management will tend to report on time and if the earnings announcement contains bad news, the management tends not to report on time. Accuracy submission of financial statements determined by the size of solvency. The lower the solvency of the more precise delivery of the financial statements, whereas the higher solvency is increasingly less precise delivery of the financial statements. Audit delay will be longer if the size of the company being audited increase. This relates to the increasing number of samples to be taken and the more extensive audit procedures that must be followed. Companies audited by KAP the big four audit will have a shorter delay than the KAP companies audited by non-big four. The company received a qualified audit opinion indicates a longer delay than that received unqualified opinion. The research objective discussions on the role of internal factors, namely firm profitability, solvency, and the size of the company and the role of external factors, namely firm size public accounting firm, the auditor's opinion, the existence of the audit committee of the duration of completion of the audit.